The Effects of The Great Depression Reflected in Arthur Miller’s Death of a Salesman - Irwan Sumarsono; Ima Masofa; Abu Fanani (ELS Journal on Interdisciplinary Studies in Humanities, 2023)
This study focused to analyze the effects of the Great Depression on the main character in Arthur Miller’s Death of a Salesman, especially on how he tried to survive, whether he succeeded or not, and the effects on his life and family. In analyzing the study, the writers used sociological and historical points of view. The writers also used the qualitative method in analyzing this study. Data were collected by doing library research. The main data were derived from the work, while the supporting data were derived from sources such as English literature journals, e-books, and other sources. The collected data were classified and analyzed before they were presented in an article. The writers used sociological and historical approaches to see the social and historical background of the play. From this study, the writers found out that Willy Loman was affected badly by the Great Depression in which he experienced difficulties both in his career as a salesman and in his life. The Great Depression had been his obstacle in gaining his dream of being a successful salesman; and having a happier, fuller, and richer family. His failure brought a serious effect that he liked to withdraw himself from the real world and lived in his illusion. The worst effect was that he could not face reality and committed suicide.